Comparison of Organic Liquid Soap Made from Papaya-Turmeric and Aloe Vera-Piper Betel - Rahmat Juninho; Irfan Afandi Syamsudin; Ismudiati Puri Handayani; Memoria Rosi; Hertiana Bethaningtyas Dyah Kusumaningrum; Yusup ABD Salam; Desti Umdatul Islamiah; Astrid Rinaldi (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2024)
In the wake of the COVID-19 pandemic, the imperative to mitigate pathogen transmission has catalyzed the innovation of soaps imbued with antimicrobial and antibacterial properties. Diverging from conventional reliance on synthetic chemicals, often associated with adverse dermatological reactions, this study explores the formulation of organic liquid soaps. These soaps leverage naturally occurring antibacterial and antimicrobial compounds from readily accessible plants, presenting a viable alternative to commercially available inorganic body washes predominantly manufactured by small to medium-sized enterprises. Specifically, this research harnesses papaya and aloe vera extracts for their antimicrobial attributes, augmented with turmeric and piper betel for enhanced antibacterial efficacy. Despite the recognized potency of turmeric and piper betel, variability in their effectiveness necessitates rigorous validation against the Indonesian National Standards (SNI) to ensure product quality and safety. This includes comprehensive evaluations of pH levels, density, Total Plate Count (TPC), and Mold and Yeast Count (MYC) to certify the soap's inhibitory capacity against bacterial and fungal proliferation. Employing maceration and hot processing techniques, the formulated papaya-based soap adhered to SNI 4085:2017 criteria for pH and MYC, although initially failing the TPC test. Subsequent incorporation of turmeric extract facilitated compliance with all SNI benchmarks. Conversely, aloe vera formulations only satisfied pH requirements under the SNI, even after adding piper betel. However, substituting piper betel with turmeric extract enabled the aloe vera soap to fulfill the requisite SNI parameters. These findings underscore turmeric extract's superior antibacterial properties, positioning it as a pivotal component in papaya and aloe vera soap formulations. Contrary to prevalent assumptions regarding piper betel's antimicrobial and antibacterial effectiveness, our investigation substantiates turmeric's superior role in bacterial growth inhibition within organic soap matrices.